SANTIAGO'S WAY TO FIND HAPPINESS IN PAULO COELHO'S THE ALCHEMIST - Zindi Nabila Onedani; Danu Wahyono (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2018)
This study is about an analysis of Santiago's way to find happiness in Paulo Coelho's The Alchemist. Psychological approach and the help of psychological theory that are used in this study to identify the reasons of Santiago's strife to pursue happiness through his journey to Egypt. From the novel, Santiago's family life background is the main reason of his strife to find happiness. The result of the study, researcher finds some indicators of happiness according to Selingma's PERMA in Santiago's journey. Santiago meets relationship, meaning and accomplishments in the end of the journey. He meets the girl, Fatima, as the love of his life. He also finds the meaning of his life, which is to live without any regrets. then, he finally finds the hidden treasure as his dream. The three indicators help Santiago to be happier than before. From the analysis, it can be found that the reason why Santiago feels happier in life is because he never stops encouraging himself with the faith of his dream, the faith of his own destiny, and the faith of his mission in life.